Organizational learning in the management team of Telemar-PA - Francircley Sampaio Nobre (2005)
This work is aimed at analyzing the organizational learning process in the managerial corps of TELEMAR - PA. This is a qualitative, descriptive, and exploratory case study conducted at the telecommunications company, TELEMAR â PA, where its managers were interviewed. In order to give support to this research, we have used a theoretical foundation made up of elements that could produce an understanding of the concepts, needs, and barriers, among other aspects, related to learning. The present study had as its aim to investigate how TELEMAR â PA develops environments that are propitious to learning, and how its administrators manage to aggregate innovation and participation as a differentiating element. The results reached through this research confirm the companyâs growth and its trend to develop in the technological aspect, however, they show discontinuity in the learning process because, although the company offers resources to this end, such as A Academia de LideranÃa and Universidade TELEMAR, it does not accomplish what it professes.